Peran Konseling Pastoral Dalam Pernikahan Anak Usia Dini Dibawah Umur 18 Tahun (International Forum of Researchers and Lecturers, 2023)
Early Childhood (AUD) is a social being who is in the age range of 0-8 years, the same thing is also stated by NAEYC. Early childhood is usually called the